Evaluation of the Influence of Atypical Vehicles on Vehicle Delays at a Signalized Intersection - Capia, Brenda (2023)
Cities in developing countries tend to have a high prevalence of atypical vehicles, therefore driving behavior characteristics and demand at intersections may vary. For this reason, the effects of rickshaw incidence on factors such as delays, queue length, and vehicular conflicts are analyzed. This is because rickshaws, being smaller in size and capacity compared to other types of transportation, can have a significant impact on traffic flow and road operations. Through the use of modeling and microsimulation techniques in Vissim 9.0, it is possible to identify the key parameters that contribute to these factors and quantify the specific impact of motorcycle taxis compared to other vehicles. Data collected and processed in the software revealed the influence of rickshaws on average travel times at an intersection, resulting in percentages of 32% for delays, 41% for vehicle conflicts, and 26% for queue lengths.